An algorithmic approach to balloon undilatable coronary lesions. Issue 2 (28th December 2022) - Rempakos, Athanasios; Kostantinis, Spyridon; Simsek, Bahadir; Karacsonyi, Judit; Allana, Salman; Egred, Mohaned; Jneid, Hani; Mashayekhi, Kambis; Di Mario, Carlo; Krestyaninov, Oleg; Khelimski, Dmitrii; Milkas, Anastasios; et al.
Abstract: Balloon undilatable lesions are lesions that have been successfully crossed by both a guidewire and a balloon but cannot be expanded despite multiple high‐pressure balloon inflations. Balloon undilatable lesions can be de novo or in‐stent. We describe a systematic, algorithmic approach to treat both de novo and in‐stent balloon undilatable lesions using various techniques, such as high‐pressure balloon inflation, plaque modification balloons, intravascular lithotripsy, very high‐pressure balloon inflation, coronary atherectomy, laser coronary angioplasty, and extraplaque lesion crossing. Knowledge of the various techniques can increase the efficiency, success and safety of the procedure.